JARINGAN DETEKTIF ANTI-TRAFFICKING âJ-TRACKâ: UPAYA MEMBENTUK ANAK SIAP DAN TANGGAP BAHAYA TRAFFICKING - Larasati, Kesumaning Dyah; Rahadyan, Gusti Aditya; Dito, Abdiel Hardwin; Puspito, Atras Radifan; Subroto, Gatot (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Indonesia was claimed as first ranked country trafficking victims contributor. Surabayaâs one of the cities in Indonesia with pretty high trafficking practices. There has been no senior high school (SMA/SMK) students act in preventing of trafficking, so as participatory approach is needed to encourage SMA/SMK students contributed actively to prevent him and others about trafficking menace. J-Trackâs using guide training system method. This system aims to create an independent, softskilled, prepared, and responsive student. The increased shown in their changed attitude indicate this program output achievementâs success and expected this J-Track program will continue to grow for the sake of usefulness